A planar stealthy antenna radome using absorptive frequency selective surface. Issue 8 (August 2014) - Chen, Qiang; Fu, Yunqi
ABSTRACT In this article, a planar stealthy radome is designed and applied to a microstrip antenna. The radome is realized using absorptive frequency selective surface (AFSS), which allows the signal at the operating frequency of antenna to pass and absorbs the out‐of‐band electromagnetic waves. The AFSS radome is placed above a microstrip antenna. Numerical and experimental results of the radiation performance and the radar cross section of the composite antenna‐radome structure have been presented. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1788–1792, 2014